Delivering the Thinking Healthy Programme for perinatal depression through volunteer peers: a cluster randomised controlled trial in Pakistan. (February 2019) - Sikander, Siham; Ahmad, Ikhlaq; Atif, Najia; Zaidi, Ahmed; Vanobberghen, Fiona; Weiss, Helen A; Nisar, Anum; Tabana, Hanani; Ain, Qurat Ul; Bibi, Amina; Bilal, Samina; Bibi, Tayyiba; et al.
Summary: Background: The Thinking Healthy Programme (THP), which is endorsed by WHO, is an evidence-based intervention for perinatal depression. We adapted THP for delivery by volunteer peers (laywomen from the community) to address the human resource needs in bridging the treatment gap, and we aimed to assess its effectiveness and cost-effectiveness in Rawalpindi, Pakistan. Methods: In this cluster randomised controlled trial, we randomly assigned 40 village clusters (1:1) to provide either THP peer-delivered (THPP) and enhanced usual care (EUC; intervention group) or EUC only (control group) to the participants within clusters. These villages were randomly selected from eligible villages by an independent researcher. The participants were pregnant women aged 18 years or older who had scored at least 10 on the Patient Health Questionnaire-9 (PHQ-9), who we recruited from households within communities in Rawalpindi, Pakistan. The research teams who were responsible for recruiting trial participants were masked to treatment allocations. Participants attended follow-up visits at 3 and 6 months after childbirth. The primary outcomes were the severity of depressive symptoms (assessed by PHQ-9 score) and the prevalence of remission (defined as a PHQ-9 score of less than 5) in participants with available data 6 months after childbirth, which was assessed by researchers who were masked to treatment allocations. We analysed outcomes by intention to treat, adjusting for covariates that were defined a priori or that showed imbalance at baseline. The trial was registered withClinicalTrials.gov, numberNCT02111915 . Findings: Between April 15 and July 30, 2014, we randomly selected 40 of 46 eligible village clusters for assessment, as per sample size calculations. Between Oct 15, 2014, and Feb 25, 2016, we identified and screened 971 women from 20 village clusters that had been randomly assigned to the THPP and EUC group and 939 women from 20 village clusters that had been randomly assigned to the EUC only group. In the intervention group, 79 women were ineligible for inclusion, 11 women refused screening, 597 women screened negative on the PHQ-9, and one woman did not consent to participate. In the control group, 75 women were ineligible for inclusion, 14 women refused screening, 562 women screened negative on the PHQ-9, and one woman did not consent to participate. We enrolled 283 (29%) women in the intervention group and 287 (31%) women in the control group. At 6 months after childbirth, 227 (80%) women in the THPP and EUC group and 226 (79%) women in the EUC only group were assessed for the primary outcome. The severity of depression (assessed by PHQ-9 scores; standardised mean difference −0·13, 95% CI −0·31 to 0·06; p=0·07) and prevalence of remission (49% in the intervention group vs 45% in the control group; prevalence ratio 1·12, 95% CI 0·95 to 1·29; p=0·14) did not significantly differ between the groups 6 months after childbirth. There was no evidence of significant differences in serious adverse events between the groups. Interpretation: THPP had no effect on symptom severity or remission from perinatal depression at 6 months after childbirth, but we found that it was beneficial on some other metrics of severity and disability and that it was cost-effective. THPP could be a step towards use of an unused human resource to address the treatment gap in perinatal depression. Funding: National Institute of Mental Health (USA).